2020
DOI: 10.1108/el-07-2019-0172
|View full text |Cite
|
Sign up to set email alerts
|

Role of visual element in spoken English discourse: implications for YouTube technology in EFL classrooms

Abstract: Purpose Recent advancements in science and technology have led to an emphasis on using technology to make education more interesting. The inclusion of computers, internet and technological media has made education more diverse, vivid and enthusiastic. The use of technology such as YouTube in education stimulates visual and auditory learning, which results in favorable outcomes. The purpose of this paper is to provide a guideline for more systematic utilization of YouTube that has been possible in Saudi EFL cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
(34 reference statements)
1
24
0
1
Order By: Relevance
“…A study by Albahiri & Alhaj (2020) was conducted to explore the elements in the stimulation of speaking skills among second language learners. The focus of the study is mainly on the theories related to technology-aided language lessons and media elements that encourage learners to interact and communicate effectively.…”
Section: Various Related Research Done Using Audio-visual Materials and The Potential Affordancesmentioning
confidence: 99%
“…A study by Albahiri & Alhaj (2020) was conducted to explore the elements in the stimulation of speaking skills among second language learners. The focus of the study is mainly on the theories related to technology-aided language lessons and media elements that encourage learners to interact and communicate effectively.…”
Section: Various Related Research Done Using Audio-visual Materials and The Potential Affordancesmentioning
confidence: 99%
“…To test the hypothesis of the study, which stated that students of private schools who start learning English at an early age have a better mastery of English than those of public school students who start at a late age, analysis of both tools' results was conducted SPSS. The results of the English language test are shown in table (1). Results obtained from data analysis of the questionnaire, as shown in table (2), revealed that most respondents agree that the early learners are better than late ones as appeared from most items responses.…”
Section: Resultsmentioning
confidence: 94%
“…Saudi translation students' performance in the translation of some Quranic euphemistic, metaphoric, polysemic, connotative expressions into English in this group scored higher than the students in the control group at p-value .05, which indicates the gains of utilizing the translation strategies. (Albahiri, et al 2020) 3.6.2 The Second Instrument…”
Section: Discussionmentioning
confidence: 99%